Other people’s dirty money: professional intermediaries, market dynamics and the finances of white-collar, corporate and organized crimes - Lord, Nicholas J. (The British journal of criminology, 2019)
This article analyses the market dynamics of the misuse of ‘corporate vehicles’ in the management of finances generated from, and for, organized, white-collar and corporate crimes. The term ‘corporate vehicles’ is a policy construct used to refer to legitimate, legal structures, like trusts and companies, that facilitate a range of commercial activities. Such vehicles also provide opportunities for those involved in serious crimes for gain to control, convert and conceal their illicit finances, usually with the assistance of professional intermediaries, such as lawyers or financial advisors. This article empirically investigates key market features (actors/providers, commodities/products, services) and conditions (supply, demand, regulation, competition), with particular focus on professional intermediaries and how they facilitate the control of other people’s dirty money.